Вы находитесь на странице: 1из 23

# ..

:
2 ,
-2
..
:
- ,
..

, 2008

:
1.

( )
) . .3
) . .4
) 7
) . ...8
) .........9
) ....9
) ....10
) . ..10
2.
) ..11
) ..13
)

1
x2

...14
3.
) ..15
) .16
) ...16
) .16
4.
. ...17
5. , . 18
6.
2

7. .22

1.

( ).
) .
, ,
:
f1(x), f2(x), f3(x), , fn(x),

(1)

,
={}.
; ,
:
f ( x) = lim f n ( x ),
n

(2)

(1)
fn(x).
,
:

u
n =1

( x ) = u1 ( x ) + u 2 ( x) +... + u n ( x ) +...

(3)

;
: f(x).
(2), fn(x)
:
f n ( x) = u1 ( x) + u 2 ( x) + ... + u n ( x) + ...

(4)

,
(1) (3),
:
u1 ( x) = f 1 ( x ),
u 2 ( x ) = f 2 ( x) f 1 ( x ),

u n ( x) = f n ( x ) f n 1 ( x ),
3

( )

f(x)

fn(x) (
), fn(x) f(x).
) .
, (2).
:

), > 0 N,
n>N

f n ( x) f ( x)

(5)

, .

, N
; .
,
, .
N;
N , ( )
?
, ,
:
1)
f n ( x) =

x
1+ n2 x2

f n ( x) = 0 ,
, f ( x) = lim
n

(0 x 1)

0 f n ( x) =

1
2nx
1

2 2
2n 1 + n x
2n

,
,

n>

1
2

f n (x)

. , ,

N = E(

1
)
2

.
() - ,
( entier,
). , (1)=1, (2,5)=2 ..
2) :
f n ( x) =

nx
f n ( x) = 0 , (0 x 1)
, f ( x) = lim
n
1+ n2 x2

x > 0
f n ( x) <

1
<
nx

n > E(

1
2

. , , n, fn(x)

[0,1] ,

f n ( x) <

1
),
x

1
2

f n ( x) =

1
.
2

x=

1
n

, n

0 1 .

1
, = 2 N,

.
:
:
1) (1) f(x)
2)

0 N,

n>N (5) ,
, (1) ( fn(x)
) f(x) .
5

, fn(x)
[0,1],
.
.
f n ( x ) = x n , (0 x 1)

3)

f n ( x) = 0 x < 1
f ( x) = lim
n

f (1) =1 .

x n < ( < 1 )
x < 1 , x n 1 , ( n)
x 1.

, .

4)

f n ( x ) = 2 n 2 x e n

2 2

(0 x 1)

[0,1] 0,
, n,

1
2n
fn ( ) =
n
e

, 0,
n.

(3).
, f(x),

n ( x ) =

k =n +1

fn(x)

n-

( x ) =f ( x ) f n ( x ) .

f n ( x ) = f ( x ) lim n ( x) = 0 .
lim
n
n

fn(x) f(x)
(, - , n (x)
), , (3)
.
:

(3), ,
, > 0
N, n>N :
f n ( x ) f ( x ) <

n (x) <

(6)

.
,

n 1
5) x ;
n =1

=(-1,1). n- : n ( x) =
n , :

lim n ( x ) =

x 1+0

1
,
2

xn
1 x

lim n ( x ) = .

x 10

, , , ,
:

n (x) <

1
( < 2 ) n .

(-1,1) ;
(-1,0] [0,1) .
) :
(3) ,
, > 0
N, n>N m=1,2,3, :
n +m

k =n +1

( x) = u n +1 ( x) + u n +2 ( x) + ... + u n +m ( x ) <

(7)

.
. (3)
:
u n ( x ) cn

(n=1,2,3,)

(8)

cn = c
n =1

+ c 2 + ... + c n + ...

(9)
7

(3) .
(8) , (3) (9) ,
(9) (3).
, ( 8) :
u n +1 ( x ) + u n +2 ( x ) +... + u n +m ( x ) c n +1 + c n +2 +... + c n +m

> 0 N, N > n
, ,
. ,
.
, ,

a
n =1

sin nx,

a
n =1

cos nx

a n , .
n =1

a n sin nx a n

an cos nx an

a n .
n =1

) .

1. un(x) (n=1,2,3,)
X=[a,b]

u
n =1

( x) = u1 ( x) + u 2 ( x) + ... + u n ( x) + ...

f(x),
.

:

1*:
f1(x), f2(x), , fn(x),

(10)

=[a,b],
f(x) , f(x) .
8

) . ,
( (1845-1918) ),
,
:

2. (1) =[a,b]
. f(x),
, .
,
:

2*. (10)
=[a,b] n f(x),
,

f n +1 ( x) f n ( x ) .

f(x) ,

fn(x) f(x) .

) :
, 1. X
, (
); X.
X,

(a , a + )

X,

. X .
, X=[a,b] X=(a,b],
X, X,
.

(a , a + ) ,

. ,
,
.
3. un(x) (x=1,2,3,)
, , :
9

lim u n ( x) = c n

(11)

(1) , 1) ,
:

c
n =1

=C

(12)

2) (1), f(), x a , :
lim f ( x) = C

(13)

) .
4. un(x) (x=1,2,3,) =[a,b]
(1) ,
f(x) (1) :
b

n =1 a

## f ( x) dx = u n ( x) dx = u1 ( x )dx + u 2 ( x) dx + ... + u n ( x) dx + ...

(14)

4*. (7) ,
=[a,b], f(x) ,
b

f ( x) dx = lim f n ( x ) dx
n

lim f n ( x ) dx = lim f n( x) dx
n

(15)

, ,
. ,
.

) .
4 :
5. un(x) (x=1,2,3,) =[a,b]
un(x) .
(1), ,
:
10

u
n =1

## ' ( x ) = u1 ' ( x ) + u 2 ' ( x ) +... + u n ' ( x) +...

(16)

f(x) (1) ,

f ' ( x ) = u n ' ( x )

(17)

n =1

2. .
) .
p(x) n:
p ( x) = a 0 + a1 x + a 2 x 2 + a3 x 3 + ... + a n x n ,

(18)

, n :
p ' ( x ) = a1 + 2 a 2 x + 3 a 3 x 2 + ... + n a n x n 1 ,
p ' ' ( x) = 1 2 a 2 + 2 3 a3 x + ... + (n 1) n a n x n 2 ,
p ' ' ( x) = 1 2 3 a3 + ... + (n 2) (n 1) n a n x n 2 ,

...................................
p ( n ) ( x) = 1 2 3 ... n a n

=0,
=0:
a 0 = p (0) , a1 =

p ' ( 0)
p ' ' (0)
, a2 =
1!
2!

a3 =

## p' ' ' (0)

,
3!

an =

p ( n ) (0 )
.
n!

(1):
p ' (0)
p' ' (0) 2 p ' ' ' (0) 3
p ( n ) (0) n
x+
x +
x + ... +
x .
1!
2!
3!
n!

p ( x ) = p (0) +

(19)

(1) .
,

-0 , 0

:
p ( x) = A0 + A1 ( x x 0 ) + A2 ( x x0 ) 2 + A3 ( x x0 ) 3 + ... + An ( x x 0 ) n .

x x0 = , p ( x) = p ( x0 + ) = P ( ) ,
2

P ( ) = A0 + A1 + A2 + A3 + ... + An
A0 = P0 (0) , A1 =

(20)

, :

P ' ( 0)
P' ' (0)
P ' ' ' (0)
, A2 =
, A3 =
1!
2!
3!

, , An =

P ( n ) ( 0)
.
n!
11

## P ( ) = p ( x0 +), P ' () = p ' ( x0 +), P ' ' ( ) = p ' ' ( x0 + ),

A0 = p ( x0 ), A1 =

p ' ( x0 )
p ' ' ( x0 )
p ' ' ' ( x0 )
p ( n ) ( x0 )
, A2 =
, A3 =
, , An =
1!
2!
3!
n!

(21)

.. (20)
=0.
(20) (21):
p ( x ) = p ( x0 ) +

p ' ( x0 )
p ' ' ( x0 )
p ' ' ' ( x0 )
p ( n ) ( x0 )
( x x0 ) +
( x x0 ) 2 +
( x x0 ) 3 + ... +
( x x0 ) n .
1!
2!
3!
n!

(22)
(22), (0=0) (19),
. , (19)
.
:

( x x0 ) n = a0 + a1 ( x x0 ) + ... + an ( x x0 ) n + ...

(23)

( x x0 ) .

,
.

( x x0 )

( ), ..

(19).
, f(x) [x0,x0+H]
[x0,x0+H]

(>0)

).
:
f ( x) = f ( x 0 ) +

f ' ( x0 )
f ' ' ( x0 )
f ( n ) ( x0 )
( x x0 ) +
( x x0 ) 2 + ... +
( x x 0 ) n + rn ( x)
1!
2!
n!

(24)

rn(x). n

( x x0 ) .

:
12

f ( x) = f ( x0 ) +

f ' ( x0 )
f ' ' ( x0 )
f ( n ) ( x0 )
( x x0 ) +
( x x0 ) 2 + ... +
( x x0 ) n + ...
1!
2!
n!

(25)

, , , ,
f(x) f(x).
(23),

a 0 = f ( x 0 ), a1 =

f ' ( x0 )
f ( n) ( x0 )
f ' ' ( x)
, a2 =
,..., a n =
,...
1!
2!
n!

.
f(x) n+1 , (20),
rn(x), , : ,
(25), ,
rn(x)
0 n: lim rn(x)=0.
0=0 f(x)
:
f ( x ) = f (0) +

f ' (0)
f ' ' (0)
f ( n ) (0)
( x) +
( x) 2 + ... +
( x) n + ...
1!
2!
n!

(26)

(6) .
rn(x)
0=0:

rn ( x ) =

(x) n +1
x
(n +1)!
( n +1)

(27)

rn ( x) =

(x)
(1 ) n x n +1
( n +1)!
( n +1)

(28)
, 0
1, n (
).
) .
,
:
13

:
f

(n)

(29)

( x) L

( L n), (26).
, rn(x) , ,
(10):

rn ( x ) =

( n +1)

(x)

( n +1)!

n +1

H n +1
.
( n +1)!

H n +1
1 +
.
n =0 ( n +1)!

H n +1
( n +1)!

0;

rn(x)

0, .
f(x)=
[-H,H], ,
f

(n)

( x) = e x ,

## . f(0)=1, f(k)(0)=1,, (26):

ex =1+

x x2 x3
xn
+
+
+ ... +
+ ...
1! 2! 3!
n!

(30)

.
1

) e x . ()
2

e x .
2

, (30)
.

1
. :
x2

1
x2

1
1
1
1
( 2 ) 2 ( 2 ) 3
( 2 ) n
2
= 1+ x + x
+ x
+ ... + x
+ ...
1!
2!
3!
n!

:
14

1
x2

= 1

1
1
1
1 1
+

+ ... + ( 2 ) n + ...
2
4
6
n! x
1!x
2!x
3!x

: (30)
.

3. .
) .
:

a
n =0

x n = a 0 + a1 x1 + a 2 x 2 + ... + a n x n + ...

a
n =0

(31)

( x x0 ) :

( x x0 ) n = a 0 + a1 ( x x0 ) + a 2 ( x x0 ) 2 + ... + a n ( x x0 ) n + ...

(0,1,2, ).

(32)

, , ..
X ={x}

, (31) .

x =x

: (1)

x =x ,

0,

, :

x x

: a n x
n =0

= a 0 + a1 x + a 2 x + ... + a n x + ...

0, , :
an x

(n=0,1,2,)

a
n =0

(33)

x x , :

x n = a 0 + a1 x + a 2 x 2 + ... + a n x n + ...

(34)

15

an x n = an x n

x
1 ) :
x

x
x

x
x

(34)

M +M

x
x
+M
x
x

+ ... + M

x
x

+ ...

, (34) .

(31) , .
: (31),
, R (

+ ),

x R (

x R

R ).

R .
) .
(1) [0,x],

x R ,

, f(x) :
x

f ( x)dx = a

) .

(31)

, f(x)
:

## f ' ( x) = na n x n 1 = a1 + 2a 2 x + ... + na n x n 1 + ...

n =1

) .

16

, ,
. ,
, , .

4.

.
f ( x) = f ( x 0 ) ,
f(x) x0 , xlim
x
0

f
,

I D( f )

## x 0 I > 0 > 0x I : x x0 < f ( x) f ( x0 ) < .

> 0 ,
,

x0 I

, > 0

x0 I

. , x0

x0 I

f I D( f ) .

I,
> 0 > 0x 0 , x I : x x0 < f ( x) f ( x0 ) <

: f(x)=sin x ,
R. > 0 = .

17

x x0,
sin x sin x 0 < .

, -
sin a a

x x0 , ,

cos(( x x 0 ) / 2) 1 ,

a R

x x0 , -,

( a=x-x0). ,

sin .
: y = f(x) [ a ; b ],
.
1: ,
X. . (:
R n )
2: f(x) [ c ; d ] (f) = sup(f(x)) inf(f(x)).

5. , .
1885 .

, .
:

f(x)

[a,b],
{Pn(x)}, f(x).
, [0,1].

Bn ( x) = f (v / n) C nv x v (1 x) n v
v =0

(32)

18

.
, n.
n

C
v =0

v
n

(1 x) n v = 1

(33)

( a + b) n

, a=x, b=1-x. ,
n

v C
v =0

v
n

x v (1 x) n v = nx

(34)

, , v=0,
:
nx

## ( n 1)(n 2) ... ( n 1 v 1 +1) v 1

x (1 x) n 1v 1
1 2 ... (v 1)

= v 1
nx C n1 (1 x ) n 1

nx
n 1

=0

n 1

x (1 x) n 1

1 (10).
n

n 2

v =0

=0

## v(v 1)C nv x v (1 x) nv = n(n 1) x 2 C n2 x (1 x) n2 = n(n 1x 2 )

, (10) n 2 x 2 , (11) (2nx-1),
(12). :
n

[ n
v =0

## x 2 ( 2nx 1)v + v(v 1)] C nv x v (1 x) n v = n 2 x 2 (2n 1)nx + n(n 1) x 2

, ,
n

(v nx)

v =0

C nv x v (1 x) n v = n x (1 x)

,
x (1 x ) =

1
1
1
( x) 2
4
2
4

(v nx)
v =0

C nv x v (1 x) n v

n
4

(35)
19

.
[0,1]. (10), :
n

f ( x) = f ( x) C nv x v (1 x) n v
v =0

(9):
n
v
Bn ( x) f ( x) = [ f ( ) f ( x)] C nv x v (1 x) n v
n
v =0

(36)

v
n

, . ,

- , , ,

f(x)

0,

## f ( x' ' ) f ( x ' ) .

(36) , 1

,
2

v
x , ,
n

, ,

v
f ( ) f ( x)
n

v
x .
n

C x (1 x) C x (1 x) =
1

=0

20

f ( x)

2M C x (1 x)
2

n
n

(v nx ) 2 2 n 2 ,

2M
2M n

n
2
n
2
2 2 2 C n x (1 x) ( nx ) 2 2 C n x (1 x) ( nx)
n
n =0
n

, (35),

M
, ( !)
2 2

Bn (x) f ( x) 2

M
.
2 2
2 n

[0,1].
[a,b]
: x=a+y(b-a),

0 y 1 .

y: f(a+y(b-a))
Bn ( y )

y [0,1].

Pn ( x ) = Bn (

x a
)
b a

f(x) x

[a,b]. .

21

,
:
[a,b] f(x)

f ( x ) = p n ( x )
n =1

.
, ,
, , ,
. , ,

.

6. .
:

; ;
;
1

; ; e x
2

; ;

;
; ,
.

22

7. :
1) .. . 1. 8-
, . . , 2006. - 448. (
. ).
2) .. . 2. 8-
, . . , 2006. - 464. (
. ).
3) .. .
- , ., - 1974.480.
4) .. . ., 1972, .2. 439 .

23

## Нижнее меню

### Получите наши бесплатные приложения

Авторское право © 2021 Scribd Inc.